Crunch Time: How to Be Your Best When It Matters Most (getAbstract Summary). - , getAbstract (linkedin.com, 2019)
Turn fear and doubt into opportunity. Review highlights from major league baseball pitching coach Rick Peterson’s book on overcoming difficult, stress-filled situations.